313 tips for trainers: a master toolkit for aspiring professionals in the domain of training and development - Ahmed, Umair; Abdul Majid, Abdul Halim; Mohd Zin, Md. Lazim (Universiti Utara Malaysia Press, 2019)
313 Tips for Trainers: A Master Toolkit for Aspiring Professionals in the Domain of Training and Development covers a wide spectrum ranging from preparing and setting the stage for training to training evaluation. Principally, the book aims to be simple, no fuss practical guide for all young trainers, who aspire to develop for a promising career in the domain of training, consultancy and employee development in particular and HR in general.